Health Service Utilization in Hong Kong During the COVID-19 Pandemic – A Cross-sectional Public Survey - Hung, Kevin KC; Walline, Joseph H.; Chan, Emily Ying Yang; Huang, Zhe; Lo, Eugene Siu Kai; Yeoh, Eng Kiong; Graham, Colin A. (International journal of health policy and management, 2022)
Background: As health systems across the world respond to the coronavirus disease 2019 (COVID-19), there is rising concern that patients without COVID-19 are not receiving timely emergency care, resulting in avoidable deaths. This study examined patterns of self-reported health service utilization, their socio-demographic determinants and association with avoidable deaths during the COVID-19 outbreak. Methods: A cross-sectional telephone survey was conducted between March 22 and April 1, 2020, during the peak rise in confirmed COVID-19 cases in Hong Kong. Cantonese-speaking Hong Kong residents over 18-years-old were recruited using a computerised random digital dialling (RDD) system. The RDD method used stratified random sampling to ensure a representative sample of the target population by age, gender, and residential district. A structured self-reported questionnaire was used. Results: Out of 1738 placed calls, 765 subjects responded to the questionnaire (44.0% response rate). The factors associated with avoiding medical consultation included being female (37.2% vs. 22.5%, P <.001), married (32.8% vs. 27%, P =.044), completing tertiary education (35.3% vs. 27.7% (secondary) vs. 14.8% (primary), P =.005), and those who reported a "large/very large" impact of COVID-19 on their mental health (36.1% vs 30.5% (neutral) vs. 19.7% (very small/small), P =.047) using logistic regression analysis. Conclusion: Married females with both higher educational attainment and concern about COVID-19 were associated with avoiding healthcare services. Timely public communication to encourage and promote early health seeking treatment even during extreme events such as pandemics are needed.